Does Historical Contingency Dictate Economic Diplomacy? Evidence From CIDCA and JICA - Widjanarko, Yeremia Nicolaus (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2024)
This study examines how the historical experiences shape the approaches of developmental agencies to economic diplomacy by focusing on CIDCA and JICA through the deep-sharp lens of Path Dependence Theory. Using qualitative comparative analysis of secondary data from official documents, academic literatures, and policy papers, this research reveals distinct patterns in how the historical contingencies influence both institutional development and aid distribution strategy. JICA, established in 1974, demonstrates classic path dependence characteristics, with its human-centred development approach and technical cooperation focus deeply rooted within Japan’s post- WW2 experience. In contrast, CIDCA, founded in 2018, shows limited path-dependent features due to its recent establishment and predetermined alignment with China’s BRI. The analysis done yields three key insights – the temporal dimensions significantly affect institutional development patterns, historical experiences shape institutional approaches differently across time periods, and aid effectiveness correlates with both of those agencies’ ability to balance historical legacies with contemporary challenges. While JICA’s longer operational history has fostered a reputation for its transparency and sustainable development, CIDCA’s strategy reflects contemporary dynamics of power through infrastructure-focused development. These findings contribute to understanding of how historical contexts influence development approaches, through limitations regarding distinct operational time frames and data availability suggest the need for continued research as CIDCA evolves.